Cambridge IGCSE biology - Mary Jones (Cambridge University Press, 2010)
Covers all aspects of the Cambridge IGCSE Biology syllabus. IGCSEBiology, Second edition matches the requirements of the revisedUniversity of Cambridge International Examinations (CIE) Biologysyllabus (0610). The series is written by an experienced IGCSEteacher, examiner and trainer, and is endorsed by CIE, ensuring thatit is up to date and comprehensive in its coverage. The Coursebookcontent has been revised and rearranged, and new material is includedon an accompanying CD-ROM in response to specific needs highlightedby practising teachers. A Workbook and a Teacher's resource are alsoavailable.